Web-based supervisor searching system for final year project students / Nurul Farhana Mohd Salim - Mohd Salim, Nurul Farhana (2015)
The degree students of Bachelor of Computer Sciences in UiTM Jasin need to carry out the final year project under supervision of the supervisor to graduate. However, based on preliminary investigation that has been done, there is a lack of attention in helping the students in Computer Science course to find a suitable lecturer to be their project’s supervisor. In order to solve this problem, a computerized system has been proposed to assist students in finding the right supervisor who has expertise matches with the research area of their project. A prototyping framework model has been adapted into this project as it can be modified from time to time to fulfil the user’s requirements. The finding of the project have been coded into several categories before the project development process. In the near future, the system should be available in mobile application since people nowadays tend to use smart phone rather than web application.